Feasting on culture and identity: food functions in a multicultural and transcultural Malaysia - Melissa Shamini Perry (Penerbit Universiti Kebangsaan Malaysia, 2017)
Malaysia is a food lover’s paradise and Malaysians in general enjoy the diverse culinary heritage of its multicultural society. Although divided by belief, culture and creed, Malaysians are united in their love for the country’s multicultural cuisine. Food is an integral factor in bringing Malaysians together and in allowing Malaysians to learn about each other’s cultures and traditions but it can also be a source of contestation and ethnic tensions. This paper explores the multifaceted functions of food in two Malaysian literary works. The paper aims to identify the role of food in the Malaysian multicultural context at both the individual and communal level. Food references, imagery, metaphors and symbols are analysed through multicultural, transcultural lenses and the postcolonial theory of the Third Space. A novel by Adibah Amin, This End of the Rainbow set in pre-independence Malaysia, and a contemporary short story Deep Fried Devils by Shih-Li Kow, are examined to investigate the transformative roles of food in the Malaysian multicultural context. These texts demonstrate the integral role of food in eliciting nostalgia of happy childhood and family memories and in forging personal and communal friendships and inter-ethnic relationships. Both the novel and short story reveal the strong connection between food and cultural identity and show how food can bring about a sense of pride and possessiveness in individuals and cultural groups and at the same time evoke power struggles and identity conflicts in a multicultural and transcultural context.